CDA OF GUS IPUL’S POLITICAL ADVERTISING IN 2018-EAST-JAVA-REGIONAL ELECTION - Moh Khoirul Anam; nurhayati nurhayati (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Recent campaign models tend to change from the traditional model which commonly happened in the past. If in the past the campaign was identical to speeches, flags, marches, etc., nowadays the campaign can be done by utilizing the digital world as a media, even though the old model is still used today in a fewer portion. Therefore, this study aims to analyze the digital campaign advertisement of Gus Ipul in East Java Election 2018. Using the Systemic Functional Grammar (SFG) theory and Critical Discourse Analysis (CDA) approach of Fairclough three-dimensional model, researchers want to reveal what message is behind the advertisements. The data in this study are five political campaign videos obtained from online video service providers, www.youtube.com. The videos are downloaded, then transcribed so that the textual data is obtained. These data are analyzed using the SFG theory. From the analysis, the results of the present study show that Gus Ipul’s political advertising is included in advocacy and contrasting advertising. Also, there are two objectives of Gus Ipul's political advertising. The first is to satire political opponents, and the second is to provide information. The information conveyed is by providing positive information, namely by using the lexicon like pengalaman - experience, paham - understanding and amanah -trustworthiness. From the political advertisement model, it can also be obtained that there are four strategies used in advertising viz emphasizing our good things, emphasizing their bad things, de-emphasizing our bad things, and de-emphasizing their good things.